Bibliometric Analysis of Research Regarding Citarum River in Indonesia and Its Implication for Government Policy - Endyana, Cipta; Hafiar, Hanny; Prastowo , Ari Agung; Fudholi, Ahmad; Amin, Kholidil (Universitas Muhammadiyah Malang, 2023)
Research mapping related to river revitalization has been carried out on areas experiencing severe pollution to provide a roadmap for knowledge and answers to a number of environmental issues surrounding rivers. Therefore, this study aims to map a number of research publications regarding the Citarum River, which is an important area for people in West Java. This river is currently the most polluted in Indonesia, which led to the implementation of the revitalization program initiated by the government known as